The SCF-FBXW7 E3 ubiquitin ligase triggers degradation of histone 3 lysine 4 methyltransferase complex component WDR5 to prevent mitotic slippage - Hänle-Kreidler, Simon; Richter, Kai; Hoffmann, Ingrid (The journal of biological chemistry, 2022)
During prolonged mitotic arrest induced by antimicrotubule drugs, cell fate decision is determined by two alternative pathways, one leading to cell death and the other inducing premature escape from mitosis by mitotic slippage. FBWX7, a member of the F-box family of proteins and substrate-targeting subunit of the SKP1-CUL1-F-Box E3 ubiquitin ligase complex, promotes mitotic cell death and prevents mitotic slippage, but molecular details underlying these roles for FBWX7 are unclear. In this study, we report that WDR5 (WD-repeat containing protein 5), a component of the mixed lineage leukemia complex of histone 3 lysine 4 methyltransferases, is a substrate of FBXW7. We determined by coimmunoprecipitation experiments and in vitro binding assays that WDR5 interacts with FBXW7 in vivo and in vitro. SKP1-CUL1-F-Box-FBXW7 mediates ubiquitination of WDR5 and targets it for proteasomal degradation. Furthermore, we find that WDR5 depletion counteracts FBXW7 loss of function by reducing mitotic slippage and polyploidization. In conclusion, our data elucidate a new mechanism in mitotic cell fate regulation, which might contribute to prevent chemotherapy resistance in patients after antimicrotubule drug treatment.